Dysobinol Extracted from Chisocheton Macrophyllus Triggers Proliferation Inhibition, Potential Apoptosis, and Cell Cycle Arrest of He La Cancer Cell Lines - Gaffar, Shabarni; Hafiz, Ersanda; Wiraswati, Hesti Lina; Ishmayana, Safri; Nurlelasari, Nurlelasari (Majalah Kedokteran Bandung, 2024)
Dysobinol is a new limonoid from C. macrophyllus seeds reported to have an anticancer activity. This study aimed to determine the cytotoxic activity of Dysobinol against HeLa cancer cell lines and evaluate its mechanism of action by determining the expression level of several carcinogenesis genes related to apoptosis and cell cycle. In this experimental study, the cytotoxic activity was determined using the MTS assay and gene expression by real-time reverse transcriptase PCR. The result shows that Dysobinol has an anticancer activity in a dose and time-dependent manner against HeLa cells and was categorized as toxic with IC50 values of 52.92, 52.70, and 14.96 μg/ml for 24, 48, and 72 hours, respectively. Dysobinol significantly increased the expression of Bax, Cas-8, and Cas-3 and decreased the expression of Cyc D1 at both doses (IC50 and 2x IC50) but only high doses (2x IC50) could affect Cas9 and NF-κB expressions, indicating that Dysobinol can induce apoptosis via the extrinsic pathway and inhibits the cell cycle through the Cyc D1 regulator. Dysobinol has the potential to be developed as a chemotherapy drug or an adjuvant agent for cervical cancer treatment.